Computer-based detection of different stages of the breast cancer using bio-potentials - Fung, Yik Yan. (2009)
Breast cancer is the second most common malignancy in women after lung cancer. Roughly ten percent of women will develop breast cancer during their lifetime, and it is also the fifth most common cause of cancer-related death.